Analysis of Impact and Sustainability in Chronic Diseases Prevention Program in XXX Highschool Balikpapan (Systematic Review) - Tarninda, Andi Amirul; Erwandi, Dadan (Jurnal Health Sains, 2024)
A healthy lifestyle requires discipline. It's not easy, particularly adolescent who feel free and are looking for their existence. Its implementaiton needs to be applied to adolescent due to many cases of chronic diseases developing among them, following their lifestyle. Sedentary/lazy to move, smoking, alcohol, lack of rest and not being able to manage mental health. Generally, adolesecent at the educational level of Junior and Senior High School. The objective of this study is to analyze aspects of the impact and sustainability of chronic disease prevention programs for adolescents. This study is a systematic review using the PRISMA (Preferred Reporting Items for Systematic Reviews & Meta Analyses) method combined with open-source search engine. The database used for searching data and information is PubMed. The keywords used during the search process are "Prevention of Chronic Disease" AND "Chronic Disease" OR "Non-communicable Disease" OR "Infectious Disease" AND “Impact of Chronic Diseases” AND “Teenagers” OR “Adolescents” AND “School”. The most variable aspects of disease prevention are more information related to chronic diseases, knowledge, attitudes and stakeholder support. The CERDIK program provides knowledge, education and information among adolescents. These factors must be taken into consideration to improve lifestyle, maintain health so that you are not vulnerable to health problems during the teenage period